The Influence of Leader Member Exchange and Work Autonomy in Improving Employee Performance with Innovative Work Behavior as a Mediating Variable at PT Jasa Raharja Bali - Satio WISOBROTO; Ida Bagus Udayana PUTRA; I Wayan Gde SARMAWA (International Journal of Environmental, Sustainability, and Social Science, 2025)
PT Jasa Raharja is one of the State-Owned Enterprises (BUMN) that has a strategic role in providing basic protection to the community related to traffic accidents. Currently, PT Jasa Raharja focuses on efforts to improve and enhance services to the community by making various innovations. This study aims to analyze the effect of leader-member exchange on employee performance with innovative behavior as a mediating variable at PT Jasa Raharja in Bali. Data collection was carried out using a questionnaire to 51 respondents who were employees at PT Jasa Raharja in Bali. Hypothesis testing is done using inferential analysis using Partial Least Squares (PLS). The results showed that Leader-Member exchange has an insignificant effect on employee performance but a positive and significant effect on employee innovative behavior. Work autonomy has a positive and significant effect on employee performance and also on innovative behavior. Innovative behavior has a positive and significant effect on employee performance. Innovative behavior is not able to mediate the effect of leader-member exchange on employee performance, but is able to mediate the effect of work autonomy on employee performance partially.